New insight into the physiologic function of Müller's muscle. (January 2021) - Leshno, Ari; Smadar, Lital; Kapelushnik, Noa; Serlin, Tal; Prat, Daphna; Priel, Ayelet; Ben Simon, Guy J.; Sagiv, Oded
Abstract: Purpose: Müller's muscle is a sympathetically innervated smooth muscle which serves as an accessory upper eyelid retractor. Its physiologic function and purpose have not yet been clearly defined. We hypothesize that sympathetic innervation to Müller's muscle serves to adjust the upper eyelid's position to variations in pupil size in response to changes in light intensity. Methods: This is a single center cross-sectional study. Healthy volunteers were asked to fixate on a distant non-accommodative target, and a video scan of the anterior segment was performed for each subject's right eye using the Heidelberg Spectralis® optical coherence tomography scanner in infrared mode. The video was taken both in photopic and scotopic conditions, recording the resultant transition of the pupil and eyelids. The pupil diameter (PD), upper eyelid margin-to-reflex distance (MRD1), lower eyelid margin-to-reflex distance (MRD2), and vertical palpebral fissure height (PFH) were measured. Results: Thirty-three healthy volunteers (19 women, 57.6%) with a median age of 40 years (range 30–58) were included. The mean PD under photopic conditions increased significantly under scotopic conditions, from 3483 ± 521 μm to 6135 ± 703 μm, respectively ( P < 0.0001). An increase in MRD1 was observed following transition from light to dark, with a mean change of 348 ± 311 μm ( P < 0.0001). There was no significant change in MRD2. Conclusions: Upper eyelid retraction occurs after transition from photopic to scotopic conditions. This movement suggests the existence of an "eyelid-light reflex" involving Müller's muscle that adjusts the position of the eyelids as the pupil dilates under scotopic conditions. Highlights: Upper eyelid position was measured under photopic and scotopic light conditions. Transition from light to dark increased MRD1 and palpebral fissure height. These change result from upper eyelid retraction in response to change in lighting. Our findings suggest the existence of an "eyelid-light reflex".